Application of ozonetherapy in the treatment of skin injuries in the elderly (Research, Society and Development, 2021)
Ozone therapy, a technique for applying ozone as a therapeutic agent, has been used for several diseases since the 19th century. The use of this element in the health area has drawn the attention of researchers, as several studies present it as an alternative to aid in the treatment of skin lesions in the elderly. The objective of this research is to identify in the scientific literature the beneficial effects of ozone therapy for the treatment of skin lesions in the elderly. Theoretical study, of the integrative literature review type, possible through a controlled search by peers in the Virtual Health Library, between July and November 2021, using the descriptors "Ozone", "Wound Healing", "Aged", associated by the Boolean operator “AND”, and selecting a sample from the full and available text filters, documents like scientific articles; year of publication 2008 to 2020; and without distinction of language. The research population included 30 documents; later, a critical and reflective reading of the titles and abstracts was carried out, and correlation with the guiding question; thus, a sample of 18 articles was established. For sample selection, a validated protocol for integrative reviews (Ursi) was used. For data analysis, five thematic categories were chosen and discussed using thematic categorical analysis, namely: antimicrobial effect, increase of O2 and energy to tissues, optimizing effect of healing, anti-inflammatory effect and control of oxidative stress. Ozone therapy as a germicidal method and its effects on the water sterilization capacity, inactivation of bacteria, viruses, fungi, yeasts and protozoa, in addition to the activation of platelets, stands out as a therapeutic in the treatment of skin lesions, especially in aged skins, can be widely and safely used in the elderly.